The Effects of Financial Literacy on Financial Preparedness For Retirement Among Academic Staff In Higher Learning Institutions In The Kingdom of Eswatini: Array - Mndzebele , Zweli W.S.; Kwenda, Farai (Acta Universitatis Danubius. Œconomica, 2020)
Objectives: The purpose of the study was to analyse the effects of financial literacy on financial preparedness for retirement among academic staff of higher learning institutions in the Kingdom of Eswatini.Prior work: Literature on personal finance suggests that employees reach retirement period with very little financial resources to support them in old age when they can no longer work. Life expectancy across the globe has increased recently and is still increasing due to advancements in science and discoveries of new drugs yet employees are still doing little to prepare for retirement. Little is known as to why employees are failing to plan for retirement when indicators show that they are likely to live longer than the previous generations. An investigation is therefore necessary to identify factors that influence financial preparedness for retirement.Approach: The study applied a quantitative methodology and a descriptive research design was adopted and used 144 respondents proportionately sampled from a population of 612 employees from higher learning institutions in Eswatini.Results: The study found that only knowledge of financial instruments significantly influences financial retirement preparedness for retirement.Implications: These findings suggest that awareness campaigns on financial products would increase financial preparedness for retirement.Value: This study contributes to the personal financial management literature by offering evidence on the relationship between financial literacy and financial preparedness for the retirement of the academic staff of institutions of higher learning in Eswatini.